Training and match demands of elite rugby union - Cousins, B. E.; Morris, J. G.; Sunderland, C.; Bennett, A. M.; Shahtahmassebi, G.; Cooper, S. B. (The Journal of Strength and Conditioning Research, 2023)
This study aimed to examine training and match demands associated with elite Rugby Union. Eighty-nine elite players were monitored using subjective (session ratings of perceived exertion) and objective (global positioning systems: distance and high-speed running [defined as >70% of individual maximum speed] distance) methods, alongside key performance indicator variables in matches (e.g., number of tackles made). These were compared between positions (forwards vs. backs) and league of competition (Premiership vs. Championship). Statistical significance was accepted as p < 0.05. Analysis revealed that backs covered greater distance (by 704 m, p < 0.001) in training and greater distance (by 7.6 m/min, p < 0.001) and high-speed running distance (by 1.22 m/min, p < 0.001) in matches, compared with forwards. In matches, the forwards experience greater key performance indicator demand (tackles: 78%; tackle assists: 207%; breakdown entries: 324%; contact events: 117%; all p < 0.001) compared with backs. The number of tackles (53%, p < 0.001) and tackles missed (35%, p = 0.001) were greater, whereas contact carries (12%, p = 0.010) and breakdown entries (10%, p = 0.024) were lower, in the Premiership compared with the Championship. Overall, these findings confirm that the running demands of Rugby Union are higher in backs, whereas contact actions are higher in forwards, with further differences between the Premiership and Championship. This comprehensive examination of the demands of elite Rugby Union could be used to ensure the specificity of training protocols for elite Rugby Union clubs, specific to both playing position (forward or back) and level of competition (Premiership or Championship).